(untitled) (AYUSHDHARA, 2022)
Background: Anal fistula is a chronic inflammatory tubular structure which is supposed to communicate with the ano-rectal canal at one end and the surface of perianal skin on the other. A classical fistula has two openings, one internal and one external. The internal opening is the primary opening and denotes the source of infection from which the fistula initially developed. During the course of its development the primary opening may sometimes close and the purulent discharge flows out through the external opening only, which is termed as ‘Blind external fistula’. The description of Bhagandara described in Ayurveda can be correlated to anal fistula. Aim: The present work aims at analyzing Arka Kshara Sutra Varti (alkaline wick) employed on non-specific inter-sphincteric Grade II Fistula-in-ano where there was no internal opening (Blind-external fistula). Materials and Methods: 15 patients of Blind external Fistula were selected for Arka Kshara Sutra Varti insertion. Arka Ksharasutra Varti prepared by cutting a small piece of Arka Ksharasutra and immersed in Jatyadi oil was inserted inside the track. The Varti was changed on alternate day upto six weeks. Assessment was done on objective (Unit Healing time- UHT) and subjective parameters. Observations: Statistically highly significant results were obtained on subjective parameters like Pain, Discharge, Itching and Burning sensation. Average Unit Healing time (U.H.T.) was 7.16 days/cm. The track became clean and healed by six weeks completely without any recurrence in the subsequent follow-up of six months. 66.67% of patients had a completely healed tract. Conclusion: Arka Ksharasutra Varti is laced with anti-bacterial, anti-fungal, bactericidal and anti- inflammatory properties which minimizes the use of antibiotics and also demolished the recurrence of symptoms. Kshara Sutra wick insertion is an effective method with negligible loss of sphincter muscle tone. The introduction of Kshara Sutra Varti in the Fistulous tract, where internal opening was not formed, is capable of dissolving the tough fibrous tissue and ultimately draining it out, thus creating a healthy base for healing.